KOMPONEN PENELITIAN - Afiyah Firiyani Apiyah; Yuly Suryandari; Rima Sahaya; Dase Erwin Juansah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Research requires research components. The research component makes research scientific, structured, and has the value that research should have. The method in this article uses a literature study method, where data is taken from several sources such as; books, journals, or other reading sources. Research components include: Role, scientific theory, variables, hypothesis, population and sample, and data